2016
DOI: 10.1186/s12960-016-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

A study of organizational versus individual needs related to recruitment, deployment and promotion of doctors working in the government health system in Odisha state, India

Abstract: BackgroundAn effective health workforce is essential for achieving health-related new Sustainable Development Goals. Odisha, one of the states in India with low health indicators, faces challenges in recruiting and retaining health staff in the public sector, especially doctors. Recruitment, deployment and career progression play an important role in attracting and retaining doctors. We examined the policies on recruitment, deployment and promotion for doctors in the state and how these policies were perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…The current distribution of specialists across CHCs could be the result of a number of factors ranging from recruitment and deployment policies of the state, to the personal choices made by doctors who, themselves, are affected by several factors such as working environment, amenities, availability of a residence, and travel times, and so on [57, 58]. A recently conducted study revealed that most postings for doctors in the state are highly politicized and it is not unusual for doctors or health workers to use their political influence to cherry-pick their desired facility.…”
Section: Discussionmentioning
confidence: 99%
“…The current distribution of specialists across CHCs could be the result of a number of factors ranging from recruitment and deployment policies of the state, to the personal choices made by doctors who, themselves, are affected by several factors such as working environment, amenities, availability of a residence, and travel times, and so on [57, 58]. A recently conducted study revealed that most postings for doctors in the state are highly politicized and it is not unusual for doctors or health workers to use their political influence to cherry-pick their desired facility.…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, career paths were seen to be important to keeping staff in service [ 34 ]. Research in India found that the tensions between organisational and individual goals can be difficult to align in postings and transfers, particularly in contexts of ambiguous or ‘pliable’ policies and staff shortage, which makes manipulation of the system from the perspective of either managers or staff possible [ 35 ]. In Nigeria, Abimbola and colleagues point to three functions of postings and transfers, including its routineness improving system performance, or punishment of staff, and how the lack of clear policy leads to differential postings and transfers practice which does not always lead to equitable distribution of staff [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Job or 'work' histories have been used in disciplines such as hospitality (9), labour market analysis (10) and health sector, more specifically occupational and environmental health (11,12). Some HRH related research also exist that use job histories as a method to examine the policy implementation (5,6,13).…”
Section: Introductionmentioning
confidence: 99%